1990
DOI: 10.1083/jcb.111.3.901
|View full text |Cite
|
Sign up to set email alerts
|

Parafusin, an exocytic-sensitive phosphoprotein, is the primary acceptor for the glucosylphosphotransferase in Paramecium tetraurelia and rat liver.

Abstract: Abstract. Parafusin, the major protein in Paramecium tetraurelia to undergo dephosphorylation in response to secretory stimuli, appears to be the primary acceptor for the glucosylphosphotransferase in this species based on five independent criteria: identical molecular size of 63 kD; identical isoelectric points in the phosphorylated state of pH 5.8 and 6.2; identical behavior in reverse-phase chromatography; immunological cross-reactivity with an affinity-purified anti-parafusin antibody; the presence of a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Previous indications on seryl-(or threonyl-) type phosphorylation sites (Murtaugh et al, 1987) may be valid, as we also found them to be sensitive to alkaline, but insensitive to acid, hydrolysis. [It was not analysed in any detail why (P)P63 forms of different pI values occur, and whether one form is glycosylated, as suggested by Satir et al (1990). ] For all these reasons we used the pI-5.95 form of P63 and of PP63 for immunolocalization studies.…”
Section: Isoforms Of Pp63mentioning
confidence: 99%
“…Previous indications on seryl-(or threonyl-) type phosphorylation sites (Murtaugh et al, 1987) may be valid, as we also found them to be sensitive to alkaline, but insensitive to acid, hydrolysis. [It was not analysed in any detail why (P)P63 forms of different pI values occur, and whether one form is glycosylated, as suggested by Satir et al (1990). ] For all these reasons we used the pI-5.95 form of P63 and of PP63 for immunolocalization studies.…”
Section: Isoforms Of Pp63mentioning
confidence: 99%
“…In this reaction, Glc-1-P is transferred from UDP-Glc to one or more mannose residues on phosphoglucomutase through the action of a membrane-bound Glc-phosphotransferase. While the purpose of this posttranslational modification of phosphoglucomutase is not yet understood, its occurrence in organisms as diverse as S. cerevisiae, Paramecium tetraurelia (26), and mammals (32) suggests that it carries out an important, conserved function. To better understand the function of the posttranslational modification of phosphoglucomutase in yeast cells, we have compared the abundance of phosphoglucomutase, its enzymatic activity, and its posttranslational modification under different physiological conditions.…”
mentioning
confidence: 99%
“…§1734 solely to indicate this fact. et al (10) have determined that in Paramecium aGlc-1-P is similarly added to mannose residues in parafusin by an aGlc-1-P phosphotransferase and that parafusin from Paramecium and the liver phosphoglycoprotein have the same major characteristics.…”
mentioning
confidence: 99%